2012
DOI: 10.1042/bj20111432
|View full text |Cite
|
Sign up to set email alerts
|

From prediction to experimental validation: desmoglein 2 is a functionally relevant substrate of matriptase in epithelial cells and their reciprocal relationship is important for cell adhesion

Abstract: Accurate identification of substrates of a protease is critical in defining its physiological functions. We previously predicted that Dsg-2 (desmoglein-2), a desmosomal protein, is a candidate substrate of the transmembrane serine protease matriptase. The present study is an experimental validation of this prediction. As demanded by our published method PNSAS [Prediction of Natural Substrates from Artificial Substrate of Proteases; Venkatraman, Balakrishnan, Rao, Hooda and Pol (2009) PLoS ONE 4, e5700], this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In our study, E-cadherin was found to be up-regulated at both the mRNA and protein levels after MCRS1 knockdown, suggesting that MCRS1 overexpression can lead to AJ disruption, cellular invasion, and tumor metastasis. 3) DSG2 is a transmembrane protein found in desmosomes and plays an important role in cell adhesion [ 28 ], the loss of which facilitates the EMT program and tumor metastasis [ 29 ]. We found that MCRS1 overexpression suppressed the expression of DSG2 mRNA, indicating that MCRS1 overexpression could impair cell adhesion and increase tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, E-cadherin was found to be up-regulated at both the mRNA and protein levels after MCRS1 knockdown, suggesting that MCRS1 overexpression can lead to AJ disruption, cellular invasion, and tumor metastasis. 3) DSG2 is a transmembrane protein found in desmosomes and plays an important role in cell adhesion [ 28 ], the loss of which facilitates the EMT program and tumor metastasis [ 29 ]. We found that MCRS1 overexpression suppressed the expression of DSG2 mRNA, indicating that MCRS1 overexpression could impair cell adhesion and increase tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, shedding of desmosomal cadherin ectodomains by cellular proteases has been reported during cancer progression and metastasis implying a role of these molecules in modulating invasion and metastasis. For example, cleavage of Dsg2 in intestinal epithelial cells by matriptase has been associated with decreased cancer cell-cell adhesion 57 . ADAM17 and 10 have also been implicated in the shedding of Dsg2 during cancer development 58 .…”
Section: Extracellular Cleavage Of Epithelial Transmembrane Junction mentioning
confidence: 99%
“…Previous studies demonstrated that serine proteases are implicated in the cleavage of desmogleins. For example, desmoglein 2 is a functional and physiological substrate of matriptase and KLK-7, 10 and KLK-5 promotes cleavage of desmoglein-1. 11 In the present study, we found that the desmoglein-3 protein level was reduced in HAI-1 KD HaCaT cells without significant alteration of its mRNA level, and treatment with the p38 inhibitor, SB203580, abrogated the reduction of desmoglein-3.…”
Section: Discussionmentioning
confidence: 99%
“…For example, matriptase, a type II transmembrane serine protease on the epithelial cell surface, degrades desmoglein-2, and kallikrein 1erelated peptidase (KLK)-5 promotes cleavage of desmoglein-1. 10,11 Hepatocyte growth factor activator inhibitor type 1 (HAI-1; official symbol SPINT1), encoded by the SPINT1 gene, is a serine protease inhibitor abundantly expressed in the placenta and in epithelial tissues. 12,13 HAI-1 regulates several trypsinlike serine proteinases, such as hepatocyte growth factor activator, matriptase, prostasin, hepsin, TMPRSS13, human airway trypsin-like protease, and KLKs 4 and 5.…”
mentioning
confidence: 99%